The challenge of genetic selection for heat tolerance: the dairy cattle example. (19th October 2016) - Carabaño, M. J.
Abstract : Exposure of livestock to high heat loads negatively affects animal's productivity. Genetic selection for heat tolerance using quantitative approaches has been developed by making use of the milk recording information merged with the meteorological information in the test date. The main conclusions of the studies following this approach have been that there is genetic variability in the response to heat stress (HS), that a genotype by environment interaction between thermal comfort and HS conditions exists and that there is a genetic antagonism between HS tolerance and high milk production. This approach has the advantage of adding no extra costs to the existing milk recording schemes, but it has some disadvantages. Current milk recording information does not seem to fully capture the productive response to high heat loads. Moreover, the antagonism between heat tolerance and high milk production may offset the benefits of selection for this trait if heat-tolerant animals are less productive. The use of new tools from phenomics, genomics and transcriptomics can help in achieving an accurate selection of heat-tolerant animals without damaging progress in milk production. New phenotypes for this selection are measure of body temperature and respiration rates together with measures of indicators of heat tolerance in milk, through the use of mid IR spectroscopy. The use of commercial DNA chips to perform genome wide association studies or comparison of whole genome DNA sequence of animals of heat adapted and temperate climate breeds could also provide useful genomic information. Finally, RNA sequencing together with the recent discovery of the possibility to use the milk transcriptome instead of tissue biopsies could help to discover differentially expressed genes under HS and thermoneutrality. The existence of powerful tools to achieve better phenotypes to identify tolerant v . susceptible animals and to gain insights about the genetic mechanisms underlying HS response to be able to disentangle the genetic puzzle of heat tolerance may make possible the selection of heat-tolerant and still productive animals.